2023
DOI: 10.1002/jum.16358
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ultrasound Semi‐Quantitative Scoring in the Diagnosis and Assessment of Gout and Hyperuricemia

Qin Shao,
Jing Wang

Abstract: ObjectivesTo develop an ultrasound semi‐quantitative scoring system for the diagnosis and evaluation of gout and hyperuricemia.MethodsThis study included 348 male patients: 81 patients with asymptomatic hyperuricemia, 182 patients with gout, and 85 patients with other arthritis. Clinical data were collected, ultrasound was detected, gout activity score was calculated to assess disease activity, and statistical analysis was performed.ResultsMonosodium urate crystal deposition and subclinical arthritis were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Several studies have reported the prevalence of subclinical US lesions related to crystal deposition in hyperuricemic individuals [ 20 , 21 , 22 , 23 ]. In a 2011 study, Pineda et al observed features of DCS at the metatarsophalangeal joint in 25% of asymptomatic subjects with hyperuricemia and they also describe other types of lesions, such as tophi and enthesophytes, but with smaller prevalence [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported the prevalence of subclinical US lesions related to crystal deposition in hyperuricemic individuals [ 20 , 21 , 22 , 23 ]. In a 2011 study, Pineda et al observed features of DCS at the metatarsophalangeal joint in 25% of asymptomatic subjects with hyperuricemia and they also describe other types of lesions, such as tophi and enthesophytes, but with smaller prevalence [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2011 study, Pineda et al observed features of DCS at the metatarsophalangeal joint in 25% of asymptomatic subjects with hyperuricemia and they also describe other types of lesions, such as tophi and enthesophytes, but with smaller prevalence [ 20 ]. Similarly, in a 2021 study, Cao et al described the prevalence of monosodium urate (MSU) crystals in 25% of patients with asymptomatic hyperuricemia [ 22 ], while in very recent study in 2023, Shao & Wang reported a less frequent occurrence of crystal deposition lesions, which were visible in only 17 individuals out of a group of 81 asymptomatic subjects with hyperuricemia [ 23 ]. Common sites at which subclinical crystal depositions occurred include the metatarsophalangeal joint, ankles, and peroneus tendons [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation